Analisis Faktor-Faktor yang Mempengaruhi Persepsi Penggunaan Informasi Akuntansi pada Pengusaha UMKM di Kecamatan Ngronggot Kabupaten Nganjuk - Eriyana Putri; Puji Astuti; Andy Kurniawan (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research is motivated by the low utilization of accounting information by Micro, Small, and Medium Enterprises (MSMEs), which can impact suboptimal business decision-making. Accounting information plays an important role in helping business actors manage operational activities, plan finances, and evaluate business performance. Therefore, this study aims to analyze the influence of accounting knowledge, business scale, and business experience on the perception of the use of accounting information, both partially and simultaneously. The approach used in this study is a quantitative approach with a causal research type. The population in this study were all MSMEs in Ngronggot District, Nganjuk Regency, totaling 162 business units. The sample used was 62 respondents, obtained through a simple random sampling technique with calculations using the Slovin formula. The data collection method was carried out by distributing questionnaires to predetermined respondents. Data analysis used multiple linear regression methods with the help of SPSS software version 27. The results of the study indicate that partially, accounting knowledge and business scale have a significant influence on the perception of the use of accounting information. This indicates that the greater the level of accounting knowledge and the larger the business scale, the higher the positive perception of the importance of using accounting information. Conversely, business experience did not show a significant partial effect, indicating that the length of time a person has been running a business does not always lead to increased use of accounting information. However, simultaneously, all three variables—accounting knowledge, business scale, and business experience—significantly influenced perceptions of the use of accounting information. This finding implies that increasing accounting knowledge and expanding business scale need to be addressed in MSME empowerment programs to optimally utilize accounting information.